The Influence of Managerial Ownership, Institutional Ownership and Deferred Tax Burden on Earnings Management in Food and Beverage Companies on the Indonesia Stock Exchange 2017 – 2021 - Kayla Puspita; Putri Zanufa Sari (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to analyze the Effect of Managerial Ownership, Institutional Ownership and Deferred Tax Burden on Profit Management in Food and Beverage Companies on the Indonesia Stock Exchange 2017 – 2021. This study used a quantitative approach in the form of financial statements of food and beverage companies listed on the Indonesia Stock Exchange from 2017 to 2021. The sampling technique used in this study used a purposive sampling approach, the number of samples used in this study were 90 samples. The results of this study indicate that managerial ownership has no effect on earnings management, institutional ownership has an effect on earnings management, deferred tax expense has an effect on earnings management, simultaneously the variables managerial ownership, institutional ownership and deferred tax expense have an effect on earnings management. The limitations in this study are that the research object only focuses on food and beverage sector companies that are listed on the Indonesia Stock Exchange from 2017 to 2021. This study uses the dependent variable, namely earnings management and independent variables, namely Managerial Ownership, Institutional Ownership and Deferred Tax Expenses As material for consideration in making decisions related to earnings management and can be used as a reference for companies in determining policies related to financial reports regarding earnings management practices. This Paper is Original Research paper.